The High-Affinity Potassium Transporter EpHKT1;2 From the Extremophile Eutrema parvula Mediates Salt Tolerance - Ali, Akhtar; Khan, Irfan Ullah; Jan, Masood; Khan, Haris Ali; Hussain, Shah; Nisar, Muhammad; Chung, Woo Sik; Yun, Dae-Jin (Frontiers in Plant Science, 2018)
To survive salt stress, plants must maintain a balance between sodium and potassium ions. High-affinity potassium transporters (HKTs) play a key role in reducing Na+ toxicity through K+ uptake. Eutrema parvula (formerly known as Thellungiella parvula), a halophyte closely related to Arabidopsis, has two HKT1 genes that encode EpHKT1;1 and EpHKT1;2. In response to high salinity, the EpHKT1;2 transcript level increased rapidly; by contrast, the EpHKT1;1 transcript increased more slowly in response to salt treatment. Yeast cells expressing EpHKT1;2 were able to tolerate high concentrations of NaCl, whereas EpHKT1;1-expressing yeast cells remained sensitive to NaCl. Amino acid sequence alignment with other plant HKTs showed that EpHKT1;1 contains an asparagine residue (Asn-213) in the second pore-loop domain, but EpHKT1;2 contains an aspartic acid residue (Asp-205) at the same position. Yeast cells expressing EpHKT1;1, in which Asn-213 was substituted with Asp, were able to tolerate high concentrations of NaCl. In contrast, substitution of Asp-205 by Asn in EpHKT1;2 did not enhance salt tolerance and rather resulted in a similar function to that of AtHKT1 (Na+ influx but no K+ influx), indicating that the presence of Asn or Asp determines the mode of cation selectivity of the HKT1-type transporters. Moreover, Arabidopsis plants (Col-gl) over-expressing EpHKT1;2 showed significantly higher tolerance to salt stress and accumulated less Na+ and more K+ compared to those over-expressing EpHKT1;1 or AtHKT1. Taken together, these results suggest that EpHKT1;2 mediates tolerance to Na+ ion toxicity in E. parvula and is a major contributor to its halophytic nature.